ความยืดหยุ่นของอุปสงค์ต่อการท่องเที่ยวของนักท่องเที่ยวชาวไทยจากแบบจำลอง AIDS (TOURISM ELASTICITIES IN THAILAND BY AIDS MODEL) - ชัยวิชญชาติ, บัณฑิต (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2020)
บทความวิจัยนี้มีวัตถุประสงค์ที่จะวัดระดับของการทดแทนกันระหว่างการท่องเที่ยวในประเทศกับการท่องเที่ยวในต่างประเทศของนักท่องเที่ยวชาวไทย จากการกำหนดระบบสมการอุปสงค์แบบ Almost Ideal System (AIDS) ของ Deaton and Muellbauer (1980) และข้อมูลรายไตรมาสตั้งแต่ไตรมาสแรกปี พ.ศ. 2549 ถึงไตรมาสที่สี่ปี พ.ศ. 2559 ผลจากการประมาณการด้วยวิธี Seemingly Unrelated Regression (SUR) เพื่อคำนวณความยืดหยุ่นต่าง ๆ สรุปได้ว่า การท่องเที่ยวมีคุณสมบัติเป็นสินค้าปกติที่มีการตอบสนองต่อราคาการท่องเที่ยวในทางตรงข้าม การท่องเที่ยวในประเทศและการท่องเที่ยวในจุดหมายต่างประเทศสามารถทดแทนซึ่งกันและกันได้ นำมาสู่ข้อเสนอแนะทางด้านนโยบาย คือ (1) การดำเนินมาตรการส่งเสริมการขยายตัวทางเศรษฐกิจมีส่วนสำคัญต่อการส่งเสริมการขยายตัวของภาคการท่องเที่ยว (2) นโยบายที่ทำให้ราคาการท่องเที่ยวลดลงสามารถส่งเสริมการขยายตัวของภาคการท่องเที่ยวได้ (3) การดำเนินมาตรการเพื่อบริหารจัดการแหล่งท่องเที่ยวให้มีความพร้อมและมีความยั่งยืน และ (4) ควรมีมาตรการเพื่อส่งเสริมให้นักท่องเที่ยวชาวไทยเดินทางท่องเที่ยวในประเทศเพิ่มขึ้น คำสำคัญ: การท่องเที่ยวไทย อุปสงค์การท่องเที่ยวไทย ความยืดหยุ่นของอุปสงค์การท่องเที่ยว This paper applies the almost ideal demand system (AIDS) to evaluate the role of substitution among Thai’s tourism destinations. There are eight choices of tourism destination for Thai tourists including Domestic, Africa, East Asia, Europe, Middle East, Oceania, South Asia and USA. The demand system of tourism destination choices of Thai tourists was estimated by employing quarterly data during 2008-2016 and applying seemingly unrelated regression (SUR) technique. First, the tourism in all destinations claim as normal goods. Second, the negative elasticities for all destinations were found. Third, the finding is that domestic destination can be substituted for all destinations Finally, the recommendations for tourism expansion are (1) the policy to enhanced the economic expansion is necessary condition to support the increasing in Thai’s demand for tourism, (2) the indirect campaign to reduce tourism price such as tax exemption should be promoted, (3) the supply management policy should be prepared to absorb the substitution of all tourism destinations, and (4) the measure to promote domestic tourism should be targeted. Keywords: Thai Tourism, Demand for Thai Tourism, Elasticities of Demand for Tourism